2011
DOI: 10.1161/hypertensionaha.110.164616
|View full text |Cite
|
Sign up to set email alerts
|

Neuromechanical Features of the Cardiac Baroreflex After Exercise

Abstract: Abstract-A single bout of exercise is associated with postexercise hypotension, transient decreases in autonomic function, and changes in baroreflex sensitivity. The baroreflex is less sensitive to falling blood pressure than to rising blood pressure; we characterized the cardiac baroreflex in terms of hysteresis and its mechanical and neural components. We hypothesized that hysteresis would be exacerbated postexercise because of a greater relative decrease in falling blood pressure. In 10 healthy young humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
0
24
1
1
Order By: Relevance
“…However, because BRS is composed of a vascular (measured as changes in arterial diameter per changes in units of BP) and an autonomic (measured as changes in heart rate (HR) per units of vascular diameter) component (Bonyhay, Jokkel, & Kollai, 1996;Kornet, Hoeks, Janssen, Willigers, & Reneman, 2002;Taylor, Willie, Ainslie, & Tzeng, 2014), their different contribution to the total BRS gain following exercise is still controversial. For example, in adults decreases in BRS following exercise have been attributed to either both components (Willie et al, 2011), or the vascular component (Studinger, Lenard, Kovats, Kocsis, & Kollai, 2003), with both components returning to baseline values 60 min post-exercise (Studinger et al, 2003;Willie et al, 2011). The difference between exercise modalities, intensities and duration makes comparisons between the results challenging, as these exercise characteristics are likely to impact BRS regulation (Halliwill et al, 2013).…”
Section: New Findingsmentioning
confidence: 99%
“…However, because BRS is composed of a vascular (measured as changes in arterial diameter per changes in units of BP) and an autonomic (measured as changes in heart rate (HR) per units of vascular diameter) component (Bonyhay, Jokkel, & Kollai, 1996;Kornet, Hoeks, Janssen, Willigers, & Reneman, 2002;Taylor, Willie, Ainslie, & Tzeng, 2014), their different contribution to the total BRS gain following exercise is still controversial. For example, in adults decreases in BRS following exercise have been attributed to either both components (Willie et al, 2011), or the vascular component (Studinger, Lenard, Kovats, Kocsis, & Kollai, 2003), with both components returning to baseline values 60 min post-exercise (Studinger et al, 2003;Willie et al, 2011). The difference between exercise modalities, intensities and duration makes comparisons between the results challenging, as these exercise characteristics are likely to impact BRS regulation (Halliwill et al, 2013).…”
Section: New Findingsmentioning
confidence: 99%
“…45 We found that following aerobic exercise baroreflex gain is reduced and hysteresis manifests. The reduction in baroreflex gain to falling blood pressure is mediated by decreased mechanical and neural gains, whereas the decreased baroreflex gain to rising blood pressure is mediated by a reduced mechanical gain only.…”
Section: Post Exercise Depression Of Baroreflex Functionmentioning
confidence: 75%
“…, Willie et al . ). Offline data processing was performed using custom written software in LabView 8.2 (National Instruments, Austin, TX, USA) on a Macintosh 3.1 GHz iMac computer (Apple, Cupertino, CA, USA).…”
Section: Methodsmentioning
confidence: 97%
“…Many activities in day‐to‐day living produce physiological challenges associated with changes in baroreflex function, such as exercise (Willie et al . ) and the assumption of an upright posture (O'Leary et al . ).…”
mentioning
confidence: 99%